2019
DOI: 10.2478/fman-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Transformational Leadership Style on Employee Engagement: The Mediating Effect of Leader’s Emotional Intelligence

Abstract: Employee engagement has been at the center of attention for human resource personnel and researchers who stated that employee engagement can be a key driver of an organization's business success. Many researchers have found in recent researches that a transformational leadership style has a beneficial connection with employee engagement. Thus, this study aims to find the causal effect of perceived transformational leadership on employee engagement through the mediating role of leader’s emotional intelligence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 15 publications
2
21
0
1
Order By: Relevance
“…Some studies have shown a relationship between transformational leadership and emotional intelligence mediating the association between emotional intelligence and counterproductive work, and the relationship between emotional intelligence and organizational commitment (Foster and Roche, 2014 ; Hussein and Yesiltas, 2020 ). Also, a recent research work showed that leaders' transformational leadership had a significant effect on employee engagement for the mediating role of emotional intelligence (Milhem et al, 2019 ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Some studies have shown a relationship between transformational leadership and emotional intelligence mediating the association between emotional intelligence and counterproductive work, and the relationship between emotional intelligence and organizational commitment (Foster and Roche, 2014 ; Hussein and Yesiltas, 2020 ). Also, a recent research work showed that leaders' transformational leadership had a significant effect on employee engagement for the mediating role of emotional intelligence (Milhem et al, 2019 ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Leader's emotional intelligence is working as a bridge between transformational leadership and employee engagement. For organizational development and employee engagement, leaders need to learn to develop high self-esteem and the art of influencing people at the workplace [33].…”
Section: Emotional Intelligence and Nature Of Leadershipmentioning
confidence: 99%
“…Meintjes and Hofmeyr (2018) found that a sense of being valued and appreciated is a key driver of positive organizational outcomes such as engagement. Milhem et al (2019) noted that employee engagement is a dyadic relationship. Employee engagement is not independent of organizational work conditions.…”
Section: Introductionmentioning
confidence: 99%